To analyze the transformation from the original function \( y = \sqrt{3 - x} \) to the new function \( y = \sqrt{3 - x} + 3 \), let's break it down.
-
Original Function: \( y = \sqrt{3 - x} \)
- This function is a square root function that opens downwards, with its maximum (at \( x = 3 \)) being 0.
-
New Function: \( y = \sqrt{3 - x} + 3 \)
- The transformation to this new function adds 3 to the entire function.
Key Transformation:
- Vertical Shift:
- Since we are adding 3 to the function, this results in a vertical shift upward by 3 units.
Conclusion:
The correct interpretation of the transformation is:
This graph represents a shift up due to the change in the y-intercept from the parent function.